Bio-Methane Potential (BMP) of Cassava Pulp Waste and Effect of Alkaline Pre-Treatment - Nguyen, Pham Hong Lien; Tran, Le Minh; Huynh, Trung Hai (JST: Engineering And Technology For Sustainable Development, 2021)
Cassava starch processing industry produces cassava pulp as a by-product or waste. In the well-known Duong Lieu village, this waste is released in surrounding environment without treatment causing serious environmental problems. The study aimed to (1) determine the Biomethane Potential (BMP) of the waste and to (2) find out if alkaline pre-treatment would improve it. Different cassava pulp samples were going through BMP test: untreated sample; pre-treated samples at different NaOH doses of 2, 6, 8 wt.% (dry weight-based) and pre-treated samples at different NaHCO₃ doses of 2, 4, 6, 8 wt.% (dry weight based). BMP assays were conducted in 590 mL bottles at 37 °C for 40 days. As the result, BMP of the untreated waste was 281 NmL CH₄/g VS and alkaline pretreatment increased BMP of the waste up to 479 mL CH₄/g VS by treatment with NaOH 6 wt.% and 450 mL CH₄/g VS by treatment with NaHCO₃ 6 wt.%. In addition, there was a significant reduction of lignin content of the substrate after alkaline pre-treatment. The results show that cassava pulp waste has moderate potential for biogas recovery. In addition, alkaline pre-treatment by either NaOH or NaHCO₃ would significantly improve its BMP, possibly thanks to the reduction of lignin content.